2003
DOI: 10.1159/000071250
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Intravenous Magnesium Therapy in Thrombolysis-Ineligible Acute Myocardial Infarction Patients

Abstract: The aim of our study was to analyze the long-term survival and cardiac function in 194 consecutive, thrombolysis-ineligible acute myocardial infarction (AMI) patients receiving 48-hour intravenous magnesium sulfate (22 g) – 96 patients, compared with placebo – 98 patients. After a mean 4.8-year follow-up, all-cause mortality and cardiac mortality were significantly lower in the magnesium compared to the placebo group [(18 vs. 33 patients, p < 0.01) and (12 vs. 30 patients, p < 0.001), respectively]. Rest radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Low serum Mg is associated with increased risk and mortality of acute MI [ 191 , 214 ], and Mg deficiency, in turn, aggravates MI by inducing mitochondrial dysfunction and increasing oxidative stress-induced ischemic injury [ 96 , 110 , 215 , 216 ]. In Mg-treated patients, there is ~20% reduction in infarct size [ 217 ], ~24%–50% decreased mortality [ 20 , 48 , 192 , 214 , 218 , 219 ], decreased rates of arrhythmias after infarction [ 48 , 217 , 218 , 219 , 220 ], increased ejection fraction [ 221 ], and improved myocardial contractile function [ 193 ]. For example, in a meta-analysis with eight clinical trials, IV Mg treatment of 930 acute MI patients showed a 49% reduction in VT/VF, a 58% reduction of incidence of cardiac arrest, and a 54% reduction in mortality [ 48 ].…”
Section: Mg Supplementation As a Therapeutic Treatment For Cardiommentioning
confidence: 99%
See 1 more Smart Citation
“…Low serum Mg is associated with increased risk and mortality of acute MI [ 191 , 214 ], and Mg deficiency, in turn, aggravates MI by inducing mitochondrial dysfunction and increasing oxidative stress-induced ischemic injury [ 96 , 110 , 215 , 216 ]. In Mg-treated patients, there is ~20% reduction in infarct size [ 217 ], ~24%–50% decreased mortality [ 20 , 48 , 192 , 214 , 218 , 219 ], decreased rates of arrhythmias after infarction [ 48 , 217 , 218 , 219 , 220 ], increased ejection fraction [ 221 ], and improved myocardial contractile function [ 193 ]. For example, in a meta-analysis with eight clinical trials, IV Mg treatment of 930 acute MI patients showed a 49% reduction in VT/VF, a 58% reduction of incidence of cardiac arrest, and a 54% reduction in mortality [ 48 ].…”
Section: Mg Supplementation As a Therapeutic Treatment For Cardiommentioning
confidence: 99%
“…For instance, oral Mg L-lactate treatment of patients with ICDs who had Mg deficiency did not reduce the occurrence of arrhythmias in ICD patients and had little impact on the health-related quality of life [ 319 ]. While several studies show that IV Mg supplementation (MgSO 4 and MgCl 2 ) improved mortality in acute MI patients [ 192 , 218 , 219 , 221 ], Feldstedt et al observed no improvement with IV MgCl 2 on either the in-hospital or the follow-up mortality after acute myocardial infarction [ 320 ]. Moreover, Mg infusion was accompanied by a significantly increased incidence of atrioventricular conduction disturbances.…”
Section: Limitations and Controversial Reports Of Mg Supplementatimentioning
confidence: 99%
“…28,29 Magnesium supplementation may be especially important given its known protective role in neuronal and myocardial injury. 28,[30][31][32] Hypothermia-induced decreases in insulin sensitivity may lead to hyperglycemia. This could enhance susceptibility to infection and also might exacerbate secondary brain injury.…”
Section: Complications Associated With Therapeutic Hypothermiamentioning
confidence: 99%